PEMAHAMAN IBU TENTANG PERMASALAHAN GIZI SERTA PERANNYA DALAM MENGATASI PERMASALAHAN GIZI BADUTA DI DESA BAN, KECAMATAN KUBU, KABUPATEN KARANGASEM, PROVINSI BALI - Sangita Pina de Canossa Belo; Dinar Saurmauli Lubis (ARCHIVE OF COMMUNITY HEALTH, 2023)
Children who don’t get nutritional intake according to their needs can cause malnutrition which affects their growth and development process. Children aged 0-2 years will generally be very dependent on their mothers, because in this age group they need breast milk and full attention. The purpose of this study was to find out about mother’s understanding of nutritional problems and their role in overcoming nutritional problems of children under two in the village of Ban, Sub-district of Kubu, District Karangasem, Bali Province. This research is a qualitative research with a descriptive approach. The main informant of this research were 10 moms with children under two years old that selected by the sampling technique used purposive sampling method. The research was conducted in 10 hamlets in Ban village, Karangasem from July-October 2019. Data collected through in-depth interview and observation. Data were analyzed using thematic analysis techniques. The results showed the mother's understanding of nutritional problems was seen from the physical condition of the child, and the mother's understanding about the causes of nutritional problems were caused by a lack of food intake. Mother's role in overcoming nutritional problems are trying to meet the nutritional needs of children, paying attention to food safety and child hygiene, utilizing health services, and doing house cleaning activities. Obstacles that barrier mother's behavior in preventing undernutrition of children under two years old are: economy, distance, dry season, child refuse to breastfeed, busy, mother's health condition, living environment, belief and limited water. Suggestions that can be given are: Health workers routinely increase counseling related to the importance of fulfilling child nutrition and environmental sanitation; Mothers should buy a breast pump when they cannot breastfeed their children directly; Karangasem Health Office conducts tests on the quality of the water that is accessed to ensure water safety, and then conducts counseling activities to the community regarding proper and correct drinking water treatment processes. Keywords: Nutrition, Understanding, Role, Ban village